The Role of XBP1 in bone metabolism - Lv, Wenhao; Zheng, Youli; Jiao, Junjun; Fu, Yu; Xu, Tingrui; Zhang, Li; Zhang, Zheng; Ma, Ning (Frontiers in Endocrinology, 2023)
Bone is a dynamic organ that, once formed, undergoes a constant remodeling process that includes bone resorption and synthesis. Osteoclasts and osteoblasts are primarily responsible for controlling this process. X-box binding protein 1 (XBP1), a transcription factor, affects the metabolism of bones in various ways. In recent years, numerous studies have revealed that XBP1 plays a vital role in bone metabolism, including osteoclast and osteoblast development, as well as in regulating immune cell differentiation that affects the immune microenvironment of bone remodeling. In this review, we highlight the regulatory mechanisms of XBP1 on osteoclasts and osteoblasts, how XBP1 affects the immune microenvironment of bone remodeling by influencing the differentiation of immune cells, and predict the possible future research directions of XBP1 to provide new insights for the treatment of bone-related metabolic diseases.